Transformational Leadership and Innovative Work Behavior Dimensions: Job Satisfaction as a Mediator in Public Healthcare - Hoiriah; Sefnedi; Dahliana Kamener (Al-Qalam Institue, 2026)
This study aims to analyze the influence of transformational leadership on innovative work behavior through its three dimensions idea generation, idea promotion, and idea realization with job satisfaction acting as a mediating variable in the context of public healthcare organizations. A quantitative explanatory approach with a cross-sectional survey design was employed. Data were collected from 152 civil servants working at a regional public hospital in Indonesia using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results reveal that transformational leadership has a positive and significant effect on idea generation, idea promotion, idea realization, and job satisfaction. Job satisfaction also shows a positive and significant influence on idea generation and idea promotion but does not significantly affect idea realization. Furthermore, mediation analysis indicates that job satisfaction partially mediates the relationship between transformational leadership and both idea generation and idea promotion, while no mediating effect is found for idea realization. These findings imply that transformational leadership and employees’ positive work attitudes play an important role in encouraging innovation in public healthcare organizations, particularly in the early stages of innovation processes, highlighting the need for leaders to foster supportive work environments that enhance employee satisfaction and innovative engagement.